Philosophy and role reflection of teaching practices in the Communication Science (extended) programme - Krige, Daleen; Bezuidenhout, Jolandi (South African Journal of Higher Education, 2016)
Higher education teachers approach their teaching practices in accordance with how they conceptualise teaching and learning. Higher education teaching and learning literature contains numerous theoretical conceptions amongst others, Carnell’s model of teaching and learning which identifies four approaches to teaching and learning: didactic, cooperative, empowering and community (Carnell 2007, 35). In the Department of Communication Science at the UFS students enrolled in the extended four-year programme attend academic facilitation sessions (AFSs) to improve their academic competencies. Since these AFSs follow the teaching and learning philosophies of experiential learning, social constructivism and cooperative learning, the AFS activities were measured against the model of Carnell (2007) to determine whether the teaching approaches used in the AFS classes are in line with these underpinning philosophies as expressed in the model by Carnell. Through critical self-reflection, the roles of the teacher and learners were identified and correlated to Carnell’s model. Results of the analysis indicate that our teaching approach is mostly empowering and cooperative and that we need to address the community approach in our teaching activities to build towards collective knowledge construction in the extended programme.